Increased Interleukin-11 Levels Are Correlated with Cardiac Events in Patients with Chronic Heart Failure. (8th January 2019) - Ye, Jing; Wang, Zhen; Ye, Di; Wang, Yuan; Wang, Menglong; Ji, Qingwei; Huang, Ying; Liu, Ling; Shi, Ying; Shi, Lei; Zeng, Tao; Xu, Yao; et al.
Abstract : Background . Interleukin-11 (IL-11) is an important inflammatory cytokine and has been demonstrated to participate in cardiovascular diseases. However, there have been no studies about the role of IL-11 in heart failure (HF). The present study is aimed at investigating whether IL-11 levels are associated with the cardiac prognosis in patients with HF. Methods . The plasma concentrations of IL-11 were measured in 240 patients with chronic HF (CHF) and 80 control subjects without signs of significant heart disease. In addition, we prospectively followed these CHF patients to endpoints of cardiac events. Results . Compared with the control group, the plasma IL-11 concentrations were significantly increased in the CHF patients and gradually increased in the New York Heart Association (NYHA) functional class II group, the NYHA functional class III group, and the NYHA functional class IV group. The receiver operating characteristic (ROC) curve revealed that the predictive role of IL-11 in HF is not as good as N-terminal B-type natriuretic peptide (BNP), although IL-11 has a certain value in predicting cardiac events. In addition, the CHF patients were divided into 3 groups according to the plasma IL-11 concentration category (low, T1; middle, T2; and high, T3). The multivariate Cox hazard analysis showed that the high plasma IL-11 concentrations were independently associated with the presence of cardiac events after adjustment for confounding factors. Furthermore, the CHF patients were divided into two groups based on the median plasma IL-11 concentrations. The Kaplan-Meier analysis revealed that the patients with high IL-11 concentrations had a higher risk of cardiac events compared with those with low IL-11 concentrations. Conclusions . Higher plasma IL-11 levels significantly increase the presence of cardiac events and suggest a poor outcome; although the diagnostic value of IL-11 in CHF is not as good as BNP, there is a certain value in predicting cardiac events in CHF.